Discretional political budget cycles and separation of powers - Jorge M. Streb; Daniel Lema; Gustavo Torrens (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
In contrast to previous empirical work on electoral cycles, which implicitly assumes the executive has full discretion over fiscal policy, this paper contends that under separation of powers an unaligned legislature may have a moderating role. Focusing on the budget surplus, we find that stronger effective checks and balances explain why cycles are weaker in developed and established democracies. Once the discretional component of executive power is isolated, there are significant cycles in all democracies. Whether the political system is presidential or parliamentary, or the electoral rules are majoritarian or proportional, does not change the basic results.
Keywords: D72; D78; 330; political budget cycles; asymmetric information; discretion; separation of powers; checks and balances; veto players; rule of law; Neue politische Ökonomie